A new variety of Impatiens jurpia (Balsaminaceae) from Arunachal Pradesh, India - Tiwari, Umeshkumar L. (Phytotaxa, 2022)
Impatiens jurpia var. ravikumareana a new variety of Balsaminaceae is described and illustrated from Arunachal Pradesh India. The new variety resembles I. jurpia var. jurpia and I. cathcartii but differ in many attributes.